2007
DOI: 10.1029/2006jd008019
|View full text |Cite
|
Sign up to set email alerts
|

Origin of C2–C5dicarboxylic acids in the European atmosphere inferred from year‐round aerosol study conducted at a west‐east transect

Abstract: [1] An atmospheric study of C 2 -C 5 dicarboxylic acids was conducted over two years at seven sites located from the Azores to eastern continental European sites. The lowest concentrations of total C 2 -C 5 diacids are observed at the Azores (Portugal) and at 4360 m elevation in the Alps ($50 ng m À3 ), and the highest (400 ng m À3) are observed at the rural K-puszta site (Hungary). Quasi-absent at surface sites, the seasonal cycle of total diacids is characterized by a pronounced summer maximum at elevated si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
181
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(201 citation statements)
references
References 47 publications
18
181
2
Order By: Relevance
“…Oxalic acid (C 2 ) is usually the dominant organic species in aerosols (Kawamura and Sakaguchi, 1999). Diacids are emitted primarily from combustion of fossil fuels, i.e., motor exhausts and coal burning, and biomass burning (Graham et al, 2002;Kawamura and Kaplan, 1987;Kundu et al, 2010a, b;Narukawa et al, 1999), but more importantly produced by the secondary oxidation of anthropogenic and biogenic volatile organic compounds (VOCs) in the atmosphere (Glasius et al, 2000;Kawamura et al, 1996a;Legrand et al, 2007). Aqueous-phase production of C 2 is also important in aerosol/cloud/fog droplets (Warneck, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Oxalic acid (C 2 ) is usually the dominant organic species in aerosols (Kawamura and Sakaguchi, 1999). Diacids are emitted primarily from combustion of fossil fuels, i.e., motor exhausts and coal burning, and biomass burning (Graham et al, 2002;Kawamura and Kaplan, 1987;Kundu et al, 2010a, b;Narukawa et al, 1999), but more importantly produced by the secondary oxidation of anthropogenic and biogenic volatile organic compounds (VOCs) in the atmosphere (Glasius et al, 2000;Kawamura et al, 1996a;Legrand et al, 2007). Aqueous-phase production of C 2 is also important in aerosol/cloud/fog droplets (Warneck, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…DCAs are found at rural (Legrand et al 2007), urban (Kawamura and Ikushima 1993), and marine sites (Kawamura and Usukura 1993), which raises questions about their sources, precursors, and formation processes. Moreover, DCAs may play a role as cloud condensation nuclei (Hori et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed a strong diurnal correlation of ozone with the oxalic acid content of aerosols (Fisseha et al 2009) and many other investigations concluded that this low-molecular weight DCA is produced mainly through oxidation of volatile organic compounds (VOCs). A brief summary of proposed precursors and formation processes of C 2 to C 6 diacids is given in Legrand et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…First, with GC the homologous series of dicarboxylic acids (C 2 -C 10 ), ketocarboxylic acids, and α-dicarbonyls can be measured (Kawamura et al, 1996a(Kawamura et al, , 2005 whereas the IC method usually measures only oxalate (Barboukas et al, 2000). If a gradient elusion technique is utilized, other species such as malonate and succinate can be determined with IC (e.g., Legrand et al, 2005Legrand et al, , 2007. Second, GC is combined on-line to mass spectrometry to obtain mass spectra of various compounds.…”
Section: Concentrations Of Oxalate (Ic) and Oxalic Acid (Gc) In Thementioning
confidence: 99%
“…Oxalic acid (C 2 ) and other low molecular weight dicarboxylic acids are the most abundant organic compound class in atmospheric aerosols from many locations on the globe including urban (Kawamura and Kaplan, 1987;Kawamura and Ikushima, 1993;Yao et al, 2004;Huang et al, 2005;Kawamura et al, 2005;Ho et al, 2007;Aggarwal and Kawamura, 2008;Hsieh et al, 2008;Miyazaki et al, 2009), remote continental (Legrand et al, 2005(Legrand et al, , 2007Kundu et al, 2010), coastal (Mochida et al, 2003a;Kawamura et al, 2004) and remote marine (Kawamura and Usukura, 1993;Kawamura and Sakaguchi, 1999;Mochida et al, 2003b;Sempéré and Kawamura, 2003) and polar regions (Li and Winchester, 1993;Kawamura et al, 1996a,b;Kerminen et al, 1999;Narukawa et al, 2003) and are abundantly present in wet precipitation samples (Sempéré and Kawamura, 1994;Kawamura et al, 2001).…”
Section: Introductionmentioning
confidence: 99%